Traditional Canister-based Open Waste Management System Versus Closed System: Hazardous Exposure Prevention and Operating Theatre Staff Satisfaction - Horn, M; Patel, N; McLellan, M; Millard, N (Operating Room Nurses Association of Canada Journal, 2016)
Introduction: Exposure to blood and body ﬂuids is a major concern to health care professionals working in operating rooms (ORs). Thus, it is essential that hospitals use fluid waste management systems that minimise risk to staff, while maximising efficiency. Method: The current study compared the utility of a ‘closed’ system with a traditional canister-based ‘open’ system in the OR in a private hospital setting. Results: A total of 30 arthroscopy, urology, and orthopaedic cases were observed. The closed system was used in five, four, and six cases, respectively and the open system was used in nine, two, and four cases, respectively. The average number of opportunities for staff to be exposed to hazardous fluids were fewer for the closed system when compared to the open during arthroscopy and urology procedures. The open system required nearly 3.5 times as much staff time for set-up, maintenance during procedures, and post-procedure disposal of waste. Theatre staff expressed greater satisfaction with the closed system than with the open. Conclusion: In conclusion, compared with the open system, the closed system offers a less hazardous and more efficient method of disposing of fluid waste generated in the OR.